2 ANTI-TANK REGIMENT, SAA - TANK AND ANTI-TANK IN THE WESTERN DESERT, 1940-1942, (PART III) - Richard Cornwell (Scientia Militaria, 2012)
In December 1941 as 'Crusader' ground to a halt, Auchinleck was already being pushed by his political masters in London to consider the complete eviction of Axis forces from North Africa. Various plans had been mooted by Churchill, who for some time past had exhorted his generals to provide a convincing victory in the one theatre where British land forces were at grips with the enemy. Operations had been suggested in which the Allies would land in French North West Africa and drive simultaneously from there and from Cyrenaica towards Tripoli. With Rommel out of Africa a start could be made with the removal of Italy from the armed camp of the Axis and the Mediterranean might be opened to Allied shipping once more.